One-Year Vision Outcomes of Age-Related Macular Degeneration in Mongolians - Ariunzaya Altankhuyag; Bayasgalan Gombojav; Sarantuya Jav; Uranchimeg Davaatseren (Central Asian Journal of Medical Sciences)
Objectives: To assess the post-treatment vision outcomes in Mongolian patients with age-related macular degeneration. Methods: Surveys assessed subjects' antioxidant intake, age, gender, race, body mass index, hypertension, smoking habits, and sunlight exposure. Results: There were 136 cases and 100 controls, of whom 130 (55.1%) were female. Of the cases, 100 individuals had the dry type of AMD, while 36 participants had the wet type of AMD. The mean ages of the dry and wet AMD groups and controls were 75.33 ± 6.98 years, 76.0 ± 5.57 years, and 67.03 ± 7.14 years, respectively-the change of central retinal thickness and intraocular pressure by month. Our current study found that the central retinal thickness of the dry AMD group did not decrease compared to the baseline. However, the value decreased from 269.9 ± 89.17 (baseline) to 218.33 ± 41.35 at the 3-month follow-up. Concerning the intraocular pressure of all subjects, the baseline pressure of the dry AMD group was 13.88 ± 3.02, and the value was increased to 14.28 ± 2.27 after one year of treatment. In the wet AMD group, the baseline value was 14.06 ± 3.58, rising to 14.42 ± 3.51 at one-year follow-up. Conclusion: A larger sample may produce different and better results.